Approximation of head and neck cancer volumes in contrast enhanced CT. Issue 1 (December 2015) - Dejaco, D.; Url, C.; Schartinger, V.; Haug, A.; Fischer, N.; Riedl, D.; Posch, A.; Riechelmann, H.; Widmann, G.
Abstract Background Tumor volume may serve as a predictor of response to radiochemotherapy (RCT) in head and neck squamous cell carcinoma (HNSCC). Computer assisted tumor volumetry requires time-consuming slice-by-slice manual or semi-automated segmentation. We questioned how accurately primary tumor and suspect cervical lymph node (LN) volumes can be approximated by the maximum tumor diameters in three dimensions. Methods In contrast-enhanced diagnostic CT scans of 74 patients with incident advanced HNSCC, manual slice-by-slice segmentation volumetry of primary tumor, total- and largest suspect cervical LN served as the reference method. In the same scans, maximum orthogonal diameters were measured using the distance measurement tool in standard visualization software in axial and coronal sections. From these diameters, approximate volumes were calculated using the cubic and ellipsoid formula. A second segmentation volumetry was performed in contrast enhanced radiotherapy-planning CT scans obtained prior to primary concurrent RCT 24 days (+/− 13 days) following the initial diagnostic CT scans. Intraclass correlation coefficients and Bland-Altman analyses were used to compare results. Results Slice-by-slice manual segmentation volumetry of primary and LN volumes revealed a lognormal distribution and ranged from 0 to 86 ml and 0 to 129 ml, respectively. Volume approximations in diagnostic CT scans with the ellipsoid formula resulted in an −8 % underestimation of tumor volumes (95 % CI −14 % to −1 %;p  = 0.022) and an −18 % underestimation of suspect cervical LN volumes (95 % CI −25 % to −12 %;p  = 0.001). Inter rater intraclass correlation for primaries was 0.95 (95 % CI +0.92 to +0.97;p  = 0.001), and intra rater intraclass correlation was 0.99 (95 % CI +0.98 to +0.99;p  = 0.001). The cubic formula resulted in pronounced overestimation of primary and LN volumes. Primary tumor volumes obtained by the second segmentation volumetry in radiotherapy-planning CT scans obtained on average 24 days following the initial volumetry resulted in larger primary tumor volumes (mean bias +28 %, 95 % CI +14 % to +41 %;p  = 0.001). Tumor volume increase correlated with time between the diagnostic and planning CTs (r  = 0.24, p  = 0.05) and was approximately 1 % per day. Discussion Ellipsoid approximations of tumor and lymph node volumes in HNSCC using maximum orthogonal diameters underestimates volumes based on segmentation in multiple slices. Due to time difference and safety margins, segmented volumes in radiotherapy-planning CT scans tend to be larger than in diagnostic CT scans. Conclusion Ellipsoid approximations of tumor and lymph node volumes in HNSCC are easily available from diagnostic CT scans. Volume estimates are applicable over a wide range of tumor and LN sizes and may be useful in clinical decision-making and oncologic research.